Hydromechanical analysis of masonry gravity dams and their foundations - Bretas, E. M. (2013)
A numerical model for the hydromechanical analysis of masonry dams based on the discrete element method is presented. The dam and the rock foundation are represented as block assemblies, and a coupled flow-stress analysis is performed in an integrated manner for the entire system. Complex block shapes may be obtained by assembling elementary blocks into macroblocks, allowing the application of the model to situations ranging from equivalent continuum to fully discontinuum analysis. A contact formulation was developed based on an accurate edge-edge approach, incorporating mechanical and hydraulic behavior. The main numerical aspects are described, with an emphasis in the flow analysis explicit algorithm. An application to an existing masonry dam is presented, analyzing its present condition, with excessive seepage, and the proposed rehabilitation intervention. An evaluation of sliding failure mechanisms was also performed, showing the expected improvement in the safety of the structure.